ADAPTIVE ENERGY-SAVING CULTIVATOR FOR STONY SOILS CULTIVATING - A. B. Kudzaev; T. A. Urtaev (Сельскохозяйственные машины и технологии)
Practice of cultivators operation on stony soils in RNO-Alania with high hardness and humidity indicates that traction resistance during the work varies widely, with deviation from the mean value by more than 2 times. Optimally adjust the machine to the soil background when using most modern mechanisms of regulation is not always possible. Customizing the data machine boils down to the choice of priority between the vibration of the working bodies in the soil, the maintenance of the given depth and power reserve stands required to crawl the working body of the big stones. It is very difficult to get in practice the best combination of these three factors, especially on stony soils. Therefore, the machine must be designed with the ability to quickly adjust to changing operating conditions and modes to ensure energy-saving effects and not violations of the specified soil depth of various hardness with the possibility of equipping the machine racks with different working bodies. The interrow cultivator with the possibility of the quick adjustment (including automated) to varying conditions was developed. In the process of studied basic parameters of elastic composite racks and parameters of pneumatic mechanism drive to adjust the proposed section of the machine were established. The system hardiness in layouts by elastic bars with air pressure up to 0.6 MPa varies from 17.7 to 45.3 N/mm. It was received effective values of pressures 0.4-0.5 MPa in the pneumatic drive partitions of the machine when operating with universal blade and ridger body OK-3 on stony soil. As a result, traction resistance decreases by 30-35 percent.